Increasing Pre-service Science Teacher Creativity Through STEM Problem-Solving - Tutut Nurita; Lia Yuliati; Muhamad Arif Mahdiannur; Fasih Bintang Ilhami; An Nuril Maulida Fauziah; Ahmad Fauzi Hendratmoko; Sapti Puspitarini (Postgraduate, University of Mataram, 2024)
Creativity is one of the skills that must be possessed in the 21st century, especially by pre-service science teachers. However, in fact, the quality of pre-service science teacher creativity still needs to be improved. Therefore, this research aims to increase the creativity of pre-service science teachers through STEM Problem-Solving. This research uses a one group pretest posttest design. The sample in this study was 53 pre-service science teachers in the science education department at Universitas Negeri Surabaya. Increasing the quality of pre-service science teacher creativity is measured based on pretest and posttest scores. The pretest and posttest scores were then analyzed using N-Change. Apart from that, it was also analyzed statistically using paired t-test. This is used to ensure that STEM Problem-Solving really has an effect on increasing the creativity of pre-service science teachers. The research results show that STEM Problem-Solving is proven to significantly increase the creativity of pre-service science teachers. The category of increasing pre-service science teacher creativity is in the medium category. The majority of pre-service science teachers' final creative quality is in the creative category.